A Rare Case of Complete Stent Fracture, Coronary Arterial Transection, and Pseudoaneurysm Formation Induced by Repeated Stenting. (12th October 2015) - Nakao, Fumiaki; Kanemoto, Masashi; Yamada, Jutaro; Suzuki, Kazuhiro; Tsuboi, Hidetoshi; Fujii, Takashi
Abstract : This report describes a rare asymptomatic case of complete stent fracture, coronary arterial transection, and pseudoaneurysm formation in response to repeated stenting. The proximal and distal ends of transected coronary artery were closed, and distal bypass was performed. Coronary arterial transection can occur in patients with repeated stenting as a long-term adverse event.